Role and effects of p38MAPK pathway inhibitors on Pinctada fucata martensii after Vibrio parahaemolyticus infection - Jie Chen; Hexin Zou; Haiying Liang; Qiyuan Zhang; Guiling Yin (Aquaculture Reports)
The SB203580 inhibitor, a blocker of the p38MAPK pathway, has been widely studied for bioimmune applications. To investigate its immune effect of Vibrio parahaemolyticus on Pinctada fucata martensii, the key genes, PmMKK6 and PmCREB, downstream of the p38MAPK pathway were cloned, and their expression analyzed following V. parahaemolyticus infection and after a postinfection injection of SB203580 inhibitor. The effects of the SB203580 inhibitor on P. f. martensii were also determined by enzyme activity and enzyme-linked immunosorbent assay (ELISA) protein quantification, as well as liver body index and histological observation. The full-length cDNA sequences of the two genes, PmMKK6 and PmCREB, were successfully cloned. And the expression of PmMKK6 and PmCREB was upregulated at different times after injection with Vibrio parahaemolyticus and showed a significant difference compared to the VC group ( P < 0.05). Significant changes in acid phosphatase (ACP) and alkaline phosphatase (AKP) enzyme activities as well as p38 protein content were also observed (all P < 0.05). The significant changes in protein expression and activity that occurred after injection of the inhibitor were also consistent with the molecular regulatory mechanisms (P < 0.05). The hepatopancreas showed significant edema and histocellular damage after infection, with an increased mortality rate compared to the control group, whereas the edematous phenotype of the hepatopancreas was alleviated after injection of the inhibitor, and damaged cells were filled with connective tissues. Vibrio parahaemolyticus stimulation activated the immunoregulatory p38MAPK pathway in P. f. martensii, while the SB203580 inhibitor successfully blocked the p38MAPK pathway, reducing the immune response to V. parahaemolyticus and providing immunoprotection to P. f. martensii. This study therefore provides insight into the mechanism of the p38MAPK pathway in the immune response process of P. f. martensii.